Analysis of Pulmonary Tuberculosis Incidence in The Community in The Talang Pangeran Health Center Area, West Pemulutan District, Ogan Ilir Regency in 2022 - Amin, Muhammad; Ekawati, Dianita; ., Yusnilasari (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2022)
Pulmonary tuberculosis is an infectious disease caused by Mycobacterium tuberculosis and is one of the top 10 causes of death worldwide. This study aims to analyze the relationship between the physical condition of the house and the incidence of pulmonary tuberculosis in the working area of the Talang Pangeran Public Health Center, Pemulutan Barat District, Ogan Ilir Regency. This research design uses a case-control approach in determining the sample using a total sampling technique for cases and purposive sampling for controls. The sample number was 96, with 32 cases and 64 control respondents. Based on bivariate using chi-square test. The variables that have a relationship with the incidence of pulmonary tuberculosis in the work area of the Talang Pangeran Public Health Center, Pemulutuan Barat District, Ogan Ilir Regency, are temperature p-Value = 0.004 (OR= 5.073; 95%CI= 1.7-14.8), humidity p-Value = 0.016 (OR= 3.4; 95%CI= 1.3-8.7), lighting p-Value = 0.048 (OR= 4.081; 95%CI= 1.1-15), roof  p-Value = 0.016 (OR= 3.182; 95%CI= 1.3-7.7). A variable that has no relationship with the incidence of tuberculosis is the type of wall p-Value = 0.828. The most dominant variable is house temperature. So that the temperature is normal, it is necessary to carry out home improvement interventions by the criteria for a healthy house. By expanding the size of the house, ventilating the house, and planting trees around the house.